Who Created the World(s) and How? A Thought Experiment Among Science Fiction, Physics, and Theology in the Novella Professor A. Dońda by Stanisław Lem - Tadeusz Sierotowicz (Religions)
This paper interprets Stanisław Lem’s novella Professor A. Dońda as a thought experiment. In the novella, Lem proposes Dońda’s law, a formulation that allows for a sophisticated theory of creation, at once theological and scientific. This is based on the equivalence of mass-energy-information and on the existence of Dońda’s barrier, which limits the accretion of knowledge. The novella is discussed in the context of Lem’s conception of the art of writing as the art of translating—in this case, translating theological issues into the language of physics and computer science. The result of this translation, which is effectively a thought experiment, is that even if man were to discover the real mechanism of the creation of the world, neither the existence of God nor the non-existence of God could be unambiguously deduced from understanding the mechanism. The protagonist of the novella articulates a theory of being whose initial premise and fundamental category is the concept of error. The paper provides a thorough analysis of the issues raised by the novella and a discussion of genre. The discussion broadens to include the context of contemporary theories in physics, mainly the mass-energy-information principle (MEIE) and the information catastrophe.